Current practices in pediatric hospital‐acquired thromboembolism: Survey of the Children's Hospital Acquired Thrombosis (CHAT) Consortium. Issue 7 (5th October 2022) - Abrams, Christina M.; Jaffray, Julie; Stillings, Amy; Branchford, Brian R.; Young, Guy; Goldenberg, Neil A.; Abajas, Yasmina L.; ,; ,
Abstract: Background: A rise in hospital‐acquired venous thromboembolism (HA‐VTE) in children has led to increased awareness regarding VTE prophylaxis and risk assessment. Despite this, no consensus exists regarding these practices in pediatrics. Objective: To describe common practices in VTE prophylaxis, VTE risk assessment models, and anticoagulation dosing strategies in pediatric hospitals that are members of the Children's Hospital Acquired Thrombosis (CHAT) Consortium. Methods: An electronic survey of 44 questions evaluating practices surrounding pediatric HA‐VTE risk assessment and prevention was distributed between August 9, 2021, and August 30, 2021, to the primary investigators from the 32 institutions within the CHAT Consortium. Results: The survey response rate was 100% ( n  = 32). In total, 85% ( n  = 27) of the institutions assess HA‐VTE, but only 63% ( n  = 20) have formal hospital guidelines. Within the institutions with formal guidelines, 100% ( n  = 20) include acute systemic inflammation or infection and presence of a central venous catheter (CVC) as risk factors for VTE. Pharmacologic prophylaxis is prescribed at 87% (28) of institutions, with enoxaparin being the most frequent (96%, n  = 27). Variability in responses persisted regarding risk factors, risk assessment, thromboprophylaxis, dosing of prophylactic anticoagulation or anticoagulant drug monitoring. A majority of providers were comfortable providing thromboprophylaxis across all age groups. In addition, the global coronavirus disease 2019 increased the providers' use of prophylactic anticoagulation 78% ( n  = 25). Conclusion: Practices among institutions are variable in regard to use of HA‐VTE prophylaxis, risk assessment, or guideline implementation, highlighting the need for further research and a validated risk assessment model through groups like the CHAT Consortium.